GAMBARAN PERILAKU PENCEGAHAN PENULARAN PENYAKIT PADA PASIEN TB PARU DI WILAYAH KERJA PUSKESMAS SINDANGKERTA TAHUN 2025 - Rohmat, Muhammad Sahrul; Rustandi, Budi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Introduction: Tuberculosis (TB) is an infectious disease that remains a global health problem, including in Indonesia. One of the factors that influence TB transmission is the patient's behavior in preventing the spread of the disease. This study aims to describe the behavior of preventing TB transmission in patients at the Sindangkerta Health Center. Methods: This study used a quantitative descriptive design with a cross-sectional approach. The sample consisted of TB patients in the Sindangkerta Health Center working area. Data were collected through a questionnaire that measured the level of knowledge, attitudes, and actions of patients related to preventing TB transmission. Data analysis was performed descriptively. Results: The results showed that the majority of patients were male compared to female. The largest age group was early adulthood, followed by late adulthood and late old age. In terms of education, the majority of patients had a high school education level, followed by elementary and junior high school. Most patients had poor preventive behavior in implementing preventive measures such as using masks, covering their mouths when coughing, and not spitting carelessly. Conclusion: Tuberculosis prevention behavior in Sindangkerta Health Center, West Bandung Regency in 2025 was poor